2012
DOI: 10.1016/j.jneuroim.2012.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Specific matrix metalloproteinase 9 (MMP-9) haplotype affect the circulating MMP-9 levels in women with migraine

Abstract: We investigated whether three relevant polymorphisms (C-1562T, microsatellite -90(CA)(14-24), and Q279R) in the MMP-9 gene, or MMP-9 haplotypes, are associated with migraine and affect MMP-9 and tissue inhibitor of MMPs (TIMP)-1 levels in patients with migraine. We studied 102 healthy women (controls) and 187 women with migraine (141 without aura - MWA, and 46 with aura - MA). Patients with MWA had higher plasma MMP-9 concentrations than patients with MA. Patients with MA had the highest TIMP-1 and lowest MMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Furthermore, Martins‐Oliveira et al . () found that combinations of MMP‐9 gene polymorphisms affected circulating MMP‐9 levels and that high MMP‐9 concentrations in patients with migraine were associated with a specific MMP‐9 haplotype.…”
Section: Pathologies: Predisposition Diagnosis and Therapy (Animal mentioning
confidence: 99%
“…Furthermore, Martins‐Oliveira et al . () found that combinations of MMP‐9 gene polymorphisms affected circulating MMP‐9 levels and that high MMP‐9 concentrations in patients with migraine were associated with a specific MMP‐9 haplotype.…”
Section: Pathologies: Predisposition Diagnosis and Therapy (Animal mentioning
confidence: 99%
“…107 MMP levels (MMP-2 and MMP-9) have been shown to be elevated post-TBI, 108 as well as in patients with migraine. 109,110 Cortical spreading depression, which has been described in stroke, head trauma, and migraine, 111 has been shown to upregulate MMP-9, with associated alterations in BBB permeability. 112 P2X 7 is a purinergic receptor on microglia activated by extracellular neuron-derived ATP that is implicated in the induction and maintenance of both neuropathic and inflammatory pain by modulating the release of cytokines that sensitize sensory nerve terminals; 113,114 P2X 7 plays a particularly important role in the release of IL-1β.…”
Section: Brain Injury and Neuroinflammationmentioning
confidence: 99%
“…Some magnetic resonance imaging studies have reported negative results [126, 127] while others have found indications of BBB leakage [128]. In migraine, indirect evidence for BBB permeabilization is provided by increased circulating levels of matrix metalloproteinases (MMPs) 2 [129] and 9 [130] that have been attributed to MMPs release from the extracellular matrix of the neurovascular unit.…”
Section: Comorbidities Of Chronic Pain With Neuroinflammatory and mentioning
confidence: 99%